The Tale of Bushy the Fox and Other Stories - Blyton, Enid; Illustrated by Biro, Val (London Award Publications Ltd., 2001)
A selection of short stories by Enid Blyton suitable for readers aged 5-8 years.
Include Illustrations
Keywords: Short stories -- Children's stories -- English fiction